2015
DOI: 10.1093/europace/euv060
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between radiofrequency with contact force-sensing and second-generation cryoballoon for paroxysmal atrial fibrillation catheter ablation: a multicentre European evaluation

Abstract: Pulmonary vein isolation using CF-guided RF and second-generation CB leads to comparable single-procedure arrhythmia-free survival at up to 18 months with similar overall complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(108 citation statements)
references
References 24 publications
4
99
2
3
Order By: Relevance
“…In a study comparing RF CA using contact force and the second-generation cryoballoon, the overall freedom from AF was similar in both groups at 18 months. However, the procedural time was shorter in the cryoablation group albeit with a higher incidence of phrenic nerve palsy 74 . The ongoing FIRE And ICE study, is a multicenter randomized control study comparing the second-generation cryoballoon to that of standard RF ablation.…”
Section: Accepted Manuscriptmentioning
confidence: 86%
“…In a study comparing RF CA using contact force and the second-generation cryoballoon, the overall freedom from AF was similar in both groups at 18 months. However, the procedural time was shorter in the cryoablation group albeit with a higher incidence of phrenic nerve palsy 74 . The ongoing FIRE And ICE study, is a multicenter randomized control study comparing the second-generation cryoballoon to that of standard RF ablation.…”
Section: Accepted Manuscriptmentioning
confidence: 86%
“…In addition, the overall complication rate was similar in the CB and CF groups (7.3 % versus 7.1 %; p=0.93). 26 In another study comparing the two techniques, 56 consecutive patients underwent a repeat ablation due to recurrent atrial tachyarrhythmias after the index PVI achieved with CF ablation (30 patients) or CB ablation (26 patients). The percentage of reconnected PVs was significantly lower following CB procedures than with CF ablation (36.1 % PVs in the CF catheter ablation group, versus 20.4 % PVs in the secondgeneration CB ablation group; p=0.01).…”
Section: Force Sensing With Rf Ablation Versus Cryo-ablationmentioning
confidence: 99%
“…Nonetheless, clinical 1-year success rate was 88% in our CF-RFA group and 88% in our CBA group, respectively. Recent studies comparing CF-guided RFA with CBA have shown statistical equivalence between the 2 technologies 25) . This may relate to the fact that even focused lesions may eliminate triggers and that not for all transmural continuous lesions around the PVs are needed [26][27][28][29] .…”
Section: Impact Of Different Technique Of Cb Ablation Vsmentioning
confidence: 99%